Development of framework for aluminum recycling management using Analytical Hierarchy Process - Hamza, Khaled Alarbi (2013)
This research focuses on the establishment of a new framework an efficient used aluminum cans management system in the context of sustainable development based on Melaka situations. The Analytical Hierarchy Process (ARP) a multi-criteria decision malting analys is was evaluated using a quantitative data generated from survey on solid waste management company in Melaka (SWM Environment Sdn Bhd and Tzu chi Foundation). Quantitative weightings from the AHP were used to identify alternative systems that have similar outcomes in meeting the aluminum cans management bjective were evaluated based on multiple criteria comprising technology, economics, quality, environment and management which were used to validate the appropriateness of the three aluminum cans management models which are recycling model, reuse and disposal model that were used. The result showed that reuse model (37.0 %) and recycling model (37.0 %) ranked first and lastly disposal model (26.0 %). The present research finding can be used to optimize aluminum cans management practices in Melaka with respect to the criteria that wereevaluated.